Effect of dietary nitrate supplementation on swimming performance in trained swimmers - Lowings, S.; Shannon, O. M.; Deighton, K.; Matu, J.; Barlow, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Nitrate supplementation appears to be most ergogenic when oxygen availability is restricted and subsequently may be particularly beneficial for swimming performance due to the breath-hold element of this sport. This represents the first investigation of nitrate supplementation and swimming time-trial (TT) performance. In a randomized double-blind repeated-measures crossover study, ten (5 male, 5 female) trained swimmers ingested 140ml nitrate-rich (~12.5mmol nitrate) or nitrate-depleted (~0.01mmol nitrate) beetroot juice. Three hours later, subjects completed a maximal effort swim TT comprising 168m (8 × 21m lengths) backstroke. Preexercise fractional exhaled nitric oxide concentration was significantly elevated with nitrate compared with placebo, Mean (SD): 17 (9) vs. 7 (3)p.p.b., p = .008. Nitrate supplementation had a likely trivial effect on overall swim TT performance (mean difference 1.22s; 90% CI -0.18-2.6s; 0.93%; p = .144; d = 0.13; unlikely beneficial (22.6%), likely trivial (77.2%), most unlikely negative (0.2%)). The effects of nitrate supplementation during the first half of the TT were trivial (mean difference 0.29s; 90% CI -0.94-1.5s; 0.46%; p = .678; d = 0.05), but there was a possible beneficial effect of nitrate supplementation during the second half of the TT (mean difference 0.93s; 90% CI 0.13-1.70s; 1.36%; p = .062; d = 0.24; possibly beneficial (63.5%), possibly trivial (36.3%), most unlikely negative (0.2%)). The duration and speed of underwater swimming within the performance did not differ between nitrate and placebo (both p > .30). Nitrate supplementation increased nitric oxide bioavailability but did not benefit short-distance swimming performance or the underwater phases of the TT. Further investigation into the effects of nitrate supplementation during the second half of performance tests may be warranted.